Major themes of the Qur'ān - Raḥmān, Fazlur (The Univ. of Chicago Press, 2009)
Fazlur Rahman (1919-88), one of the most important Muslim scholars of the twentieth century, devoted his career to helping students understand the Qur'an's teachings about God, man, and society. Back in print for a new generation of students and scholars to discover, "Major Themes of the Qur'an" is his introduction to one of the richest texts in the history of religious thought. In this classic work, Rahman unravels the Qur'an's complexities with the deep attachment of a Muslim educated in Islamic schools and the clarity of a scholar who taught for decades in the West. - God -- Man as individual -- Man in society -- Nature -- Prophethood and revelation -- Eschatology -- Satan and evil -- Emergence of the Muslim community -- Appendix I: The religious situation of the Muslim community in Mecca -- Appendix II: The people of the book and diversity of religions.